2011
DOI: 10.2460/ajvr.72.5.608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of duration and type of anesthetic on tear production in dogs

Abstract: Results suggested that inhalant anesthetics did not reduce tear production after anesthesia and that longer-duration anesthesia did not cause decreased tear production, compared with shorter-duration anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 23 publications
4
33
0
3
Order By: Relevance
“…A normal to slightly lower than normal IOP, a central and fixed globe, and physiological tear production are desirable before and during ocular surgery (Murphy 1985, Herring and others 2000, Gross and Giuliano 2007). In dogs, these ocular parameters have been investigated after the administration of methoxyflurane (Vassilieff 1976), flumazenil (Artru 1991), medetomidine (Verbruggen and others 2000, Wallin-Håkanson and Wallin-Håkanson 2001), sevoflurane, desflurane (Almeida and others 2004), nitrous oxide (Almeida and others 2008), thiopental (Hofmeister and others 2008), propofol (Batista and others 2000, Hofmeister and others 2008, 2009, Hasiuk and others 2013), ketamine–midazolam (Ghaffari and others 2010), isoflurane (Shepard and others 2011) and dexmedetomidine (Artigas and others 2012). To the authors’ knowledge, the effect of a single intravenous bolus of alfaxalone on ocular parameters has not been previously investigated in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…A normal to slightly lower than normal IOP, a central and fixed globe, and physiological tear production are desirable before and during ocular surgery (Murphy 1985, Herring and others 2000, Gross and Giuliano 2007). In dogs, these ocular parameters have been investigated after the administration of methoxyflurane (Vassilieff 1976), flumazenil (Artru 1991), medetomidine (Verbruggen and others 2000, Wallin-Håkanson and Wallin-Håkanson 2001), sevoflurane, desflurane (Almeida and others 2004), nitrous oxide (Almeida and others 2008), thiopental (Hofmeister and others 2008), propofol (Batista and others 2000, Hofmeister and others 2008, 2009, Hasiuk and others 2013), ketamine–midazolam (Ghaffari and others 2010), isoflurane (Shepard and others 2011) and dexmedetomidine (Artigas and others 2012). To the authors’ knowledge, the effect of a single intravenous bolus of alfaxalone on ocular parameters has not been previously investigated in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, halothane has been shown to do the same in dogs when combined with thiamylal (Ludders and Heavner 1979). Isoflurane and desflurane, as sole agents, have also been recently reported to decrease tear production in dogs regardless of the duration of anaesthesia and type of anaesthetic used (Shepard and others 2011). Inhibition of tears has also been documented in human beings with the use of inhalant gas anaesthesia (Cross and Krupin 1977, Krupin and others 1977) with various inhalation agents used (nitrous oxide-oxygen, halothane and enflurane) (Krupin and others 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Herring et al (2000) reported that tear production was decreased during and for up to 24 h after general anesthesia and that general anesthesia lasting more than 2 h had a significantly greater impact on postoperative tear production than shorter procedures. 6 Conversely, Shepard et al (2011) demonstrated that tear production returned to normal immediately after short (1 h) and long (4 h) episodes of anesthesia when either isoflurane or desflurane was used as the sole anesthetic agent. 7 Multiple drugs (premedicants, injectable induction agents) were used in the earlier study, including atropine, which may account for the different findings.…”
Section: Tear Productionmentioning
confidence: 99%
“…6 Conversely, Shepard et al (2011) demonstrated that tear production returned to normal immediately after short (1 h) and long (4 h) episodes of anesthesia when either isoflurane or desflurane was used as the sole anesthetic agent. 7 Multiple drugs (premedicants, injectable induction agents) were used in the earlier study, including atropine, which may account for the different findings. General anesthesia with sevoflurane after morphine, acepromazine, as well as after no premedication also reduced tear production during anesthesia.…”
Section: Tear Productionmentioning
confidence: 99%